Soluble Gamma-secretase Modulators Attenuate Alzheimer's β-amyloid Pathology and Induce Conformational Changes in Presenilin 1 - Raven, Frank (EBioMedicine, 2017)
A central pathogenic event of Alzheimer's disease (AD) is the accumulation of the Aβ42 peptide, which is generated from amyloid-β precursor protein (APP) via cleavages by β- and γ-secretase. We have developed a class of soluble 2-aminothiazole γ-secretase modulators (SGSMs) that preferentially decreases Aβ42 levels. However, the effects of SGSMs in AD animals and cells expressing familial AD mutations, as well as the mechanism of γ-secretase modulation remain largely unknown. Here, a representative of this SGSM scaffold, SGSM-36, was investigated using animals and cells expressing FAD mutations. SGSM-36 preferentially reduced Aβ42 levels without affecting either α- and β-secretase processing of APP nor Notch processing. Furthermore, an allosteric site was identified within the γ-secretase complex that allowed access of SGSM-36 using cell-based, fluorescence lifetime imaging microscopy analysis. Collectively, these studies provide mechanistic insights regarding SGSMs of this class and reinforce their therapeutic potential in AD.